The use of bio-waste to revegetate eroded land areas in Ylläs, Northern Finland : toward a zero waste perspective of tourism in the Finnish Lapland - Piippo, Sari; Juntunen, Antti; Kurppa, Sirpa; Pongràcz, Eva (Resources, Conservation and Recycling)
2014